2022
DOI: 10.1371/journal.pone.0274530
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the effect of low temperature treatment on trichome density and related differentially expressed genes in Chinese cabbage

Abstract: Trichome is important for help plant resist adversity and external damage. However, it often affects the appearance and taste of vegetables. In the present study, the trichome density of leaves from two Chinese cabbage cultivars with and without trichomes treated at low temperature are analyzed by biological microscope, and the differentially expressed genes related to trichomes formation were screened through transcriptome sequencing. The results showed that the number of leaves trichomes was reduced by 34.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
2
0
0
Order By: Relevance
“…As trichomes are known to be involved in several abiotic stresses (Wang et al, 2021) including cold tolerance, trichome density and architecture were studied in plant leaves grown under W light. As shown in previous studies, low-temperature stress resulted in varied alterations (either lower or higher) in trichome density (Sun et al 2022;Zhang et al, 2020 ) across different plant species. In the Col-0 line trichome density was increased by 2.9-fold under lower temperature (Figure 6A & 6B).…”
Section: Altered Trichome Morphology Contributes To Cold Resistance I...supporting
confidence: 70%
“…As trichomes are known to be involved in several abiotic stresses (Wang et al, 2021) including cold tolerance, trichome density and architecture were studied in plant leaves grown under W light. As shown in previous studies, low-temperature stress resulted in varied alterations (either lower or higher) in trichome density (Sun et al 2022;Zhang et al, 2020 ) across different plant species. In the Col-0 line trichome density was increased by 2.9-fold under lower temperature (Figure 6A & 6B).…”
Section: Altered Trichome Morphology Contributes To Cold Resistance I...supporting
confidence: 70%
“…But there is still a lack of systematic study in this area. At present, this study has confirmed that some exogenous hormones have a certain inhibitory effect on the early bolting of plants and at the same time can improve the quality of medicinal materials, which has been confirmed in plants such as A. sinensis [36], A. dahurica [37], and B. rapa [38]. In the study of genes related to bolting in K. praeruptora, researchers employed a combination of transcriptome sequencing and co-expression analysis to elucidate the regulatory mechanisms of key genes involved in coumarin synthesis and the formation of other active ingredients before and after bolting [39,40].…”
Section: Cultivationsupporting
confidence: 52%